Tumor biology influences the prognosis of nephroblastoma patients with primary pulmonary metastases: results from SIOP 93-01/GPOH and SIOP 2001/GPOH - Warmann, Steven; Furtwängler, Rhoikos; Blumenstock, Gunnar; Armeanu, Sorin; Nourkami, Nasenien; Leuschner, Ivo; Schenk, Jens-Peter; Graf, Norbert; Fuchs, Jörg (Annals of surgery, 2011)
Objective: To analyze the outcome of Wilms' tumor patients with primary lung metastases. Summary background data: Radiotherapy and/or surgery are used for local control of primary pulmonary Wilms' tumor metastases. A widely accepted treatment standardization is still lacking. Methods: Data for 210 patients with Wilms' tumor and primary lung metastases from the collaborative multicenter trials SIOP 93-01/GPOH and SIOP 2001/GPOH of the German Society of Pediatric Oncology and Hematology were reviewed. Analyses included patient data, tumor characteristics, local treatment, outcome and possible prognostic factors. Results: Five-year overall survival (OS) was 83.3% and 5-year event free survival (EFS) was 72.3% for all children. Survival was significantly poorer in children with high risk primary tumor histology (OS 44.4%) compared to low risk (OS 100.0%) and intermediate risk histology (OS 89.2%, P < 0.001). Within the high risk group, tumors of the blastemal subtype (OS 56.5%) were associated with a significantly better outcome than those presenting with diffuse anaplasia (OS 22.2%, P = 0.02). Further, prognostic markers were lacking response to chemotherapy (P = 0.011), persistence of metastases after local treatment (P = 0.007), and vitality of metastases (P = 0.01). Conclusions: The prognosis of children with primary Wilms' tumor lung metastases mainly depends on the biology of primary tumors and metastases and is excellent with adequate treatment. Pulmonary metastasectomy is indicated if complete remission can be achieved to avoid lung irradiation. In the future a standardized local approach to nonresponding lung metastases (metastasectomy, irradiation, or both) will have to be prospectively evaluated regarding outcome, acute toxicity, and late effects.
Gesehen am 07.11.2022